2001
DOI: 10.1562/0031-8655(2001)073<0630:npppoh>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Photosynthesis: Photocatalytic Production of Hydrogen by Platinized Photosystem I Reaction Centers¶

Abstract: A study of the photocatalytic production of molecular hydrogen from platinized photosystem I (PSI) reaction centers is reported. At pH 7 and room temperature metallic platinum was photoprecipitated at the reducing end of PSI according to the reaction, [PtCl6]2- + 4e- + hv-->Pt decreases + 6Cl-, where it interacted with photogenerated PSI electrons and catalyzed the evolution of molecular hydrogen. The reaction mixture included purified spinach PSI reaction centers, sodium ascorbate and spinach plastocyanin. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 16 publications
(15 reference statements)
1
56
0
Order By: Relevance
“…Different bioelectrochemical devices that implement the RC, PSI and/or PSII as light harnessing components for the activation of PBFCs producing photocurrents [19][20][21][22] , or fuel products [23][24][25] have been proposed. These PBFCs require the immobilization and electrical contacting of the light harnessing components with the electrode supports to the extent that photo-induced electrontransfer processes occur between the photosynthetic RC, thus enabling the generation of photocurrents (or their use for the synthesis of fuel products).…”
mentioning
confidence: 99%
“…Different bioelectrochemical devices that implement the RC, PSI and/or PSII as light harnessing components for the activation of PBFCs producing photocurrents [19][20][21][22] , or fuel products [23][24][25] have been proposed. These PBFCs require the immobilization and electrical contacting of the light harnessing components with the electrode supports to the extent that photo-induced electrontransfer processes occur between the photosynthetic RC, thus enabling the generation of photocurrents (or their use for the synthesis of fuel products).…”
mentioning
confidence: 99%
“…2a. Our apparatus mimics a similar system at Oak Ridge National Laboratory, which has been described previously in a number of biohydrogen experiments [13,14,16,[19][20][21], with Table 1. The custom bioreactor designed for this system is shown in Fig.…”
Section: Setup Of Hydrogen Production Bioreactor and Detection Apparatusmentioning
confidence: 99%
“…6 is a schematic illustration of a platinized PSI reaction center. We have shown that the coupled system of platinized PSI reaction centers, sodium ascorbate and plastocyanin is capable of sustained photoevolution of molecular hydrogen [2]. Since the midpoint redox potential of hydrogen evolution at pH 7 is more negative than -0.4 V, vs. the normal …”
Section: Resultsmentioning
confidence: 99%
“…The following results are reported: (1) measurement of open circuit electrostatic potentials from isolated PSI reaction centers [1]; (2) measurement of hydrogen photoevolution from platinized PSI reaction centers under closed circuit conditions using the rate of hydrogen evolution as a measure of current flow [2]; (3) measurement of functional PSI activity after they have been inserted into the liposomes. 6 is a schematic illustration of a platinized PSI reaction center.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation